RETRACTED: Modeling of stationary mode for pipeline operation during hot oil pumping - Fugarov D.D.; Purchina O.A.; Purchina A.D. (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001